Implementation and application of functional languages 22nd international symposium, IFL 2010, Alphen aan den Rijn, The Netherlands, September 1-3, 2010, revised selected papers - IFL 2010 (2010 Alphen aan den Rijn, Netherlands); Hage, Jurriaan; Morazán, Marco T. (Berlin, Heidelberg Springer, 2011)
This book constitutes the thoroughly refereed post-proceedings of the 22nd International Workshop on Implementation and Applications of Functional Languages, IFL 2011, held in Alphen aan den Rijn, The Netherlands in September 2011. The 13 revised full papers presented were carefully reviewed and were selected from 31 submissions. The IFL symposia bring together researchers and practitioners that are actively engaged in the implementation and the use of functional and function based programming languages. Every year IFL provides a venue for the presentation and discussion of new ideas and concepts, of work in progress, and of publication-ripe results.
Electronic reproduction.
Keywords: Functional programming languages -- Congresses; Electronic books